(untitled) (Al-Qamar, 2025)
Allah Almighty bestowed the seal of prophethood upon the beloved Prophet Muhammad (peace be upon him), and in the Quran, He took it upon Himself to safeguard this honor until the Day of Judgment: "Muhammad is not the father of any of your men, but he is the Messenger of Allah and the Seal of the Prophets" (Quran, Al-Ahzab 33:40). This profound honor and responsibility ensure that no one can ever challenge or alter the finality of prophethood, as Allah Himself has guaranteed its protection. In pursuit of this sacred mission, the “Shuban Khatm-e-Nubuwwat Institute” dedicates its full efforts and resources to protecting the finality of prophethood. The institute is tirelessly working day and night to guide and support individuals who have converted from Qadianism to Islam, assisting them in their religious, social, and economic development. Their work involves not only providing proper Islamic education and guidance but also offering educational support, healthcare services, and employment opportunities to help these individuals lead dignified lives within society. The organization’s efforts are focused on clarifying the misconceptions of Qadianism and promoting the true teachings of Islam. Key initiatives include educational assistance, healthcare provisions, and job opportunities, which collectively bring significant positive changes to the lives of converts from Qadianism. This paper aims to provide a comprehensive overview of the Shuban Khatm-e-Nubuwwat Institute’s activities and their impact, highlighting how their endeavors have led many to embrace Islam and live a positive and fulfilling life.